(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Globally, the environment is becoming a far more criticaleconomic, social, and political issue.Promoting economic development and preserving the environment are two issues that the world is nowdealing with.A sustainable development at this point requires thorough assessment of environmental effects oneconomic development. It has been noted that numerous efforts have been made to provide a frameworkfor combining national income and environmental data to compute economic development. Additionally,none of these initiatives address the microeconomic component of environmental data, which is therelationship between a particular firm and the environment. To identify the sustainability gap at the microlevel, an accounting of the relationship between the firm and the environment is necessary.The emergence of corporation level environmental accounting and its attendant issues are bothaddressed in this paper. 15 sample Indian businesses are being considered for the study while reportingand accounting procedures are taken into consideration. The annual reports for 15 sample firms’ 2021–2022 accounting seasons were examined for figures. These companies were picked from a list of the top50 corporations listed on the National Stock Exchange.The report offers a thorough overview of recentresearch on several environmental accounting aspects of a sample companies and how they relate tocorporate sustainability. In terms of profitability, financial leverage, industry type, and the social andmoral responsibility of environmental accounting, we found that there was a significant discrepancy.According to a study, environmental reporting is now included in annual reporting in India, which iswidely accepted as a result of the increase in stakeholder environmental awareness. The bulk of Indiancompanies report annually on their environmental initiatives. Based on these fascinating findings, it wassuggested that standard-setters should give in to the persistent pleas and suggestions made by eminentacademics for guidelines pertaining to the formation of Financial Reporting Standards on environmentalaccounting (EA) in order to improve corporate sustainability.